A Method for Quantitative 3D Mesoscale Analysis of Solid Oxide Fuel Cell Microstructures Using Xe-plasma Focused Ion Beam (PFIB) Coupled with SEM. (30th May 2017) - Mahbub, Rubayyat; Hsu, Tim; Epting, William K; Nuhfer, Noel T.; Hackett, Gregory A; Abernathy, Harry; Rollett, Anthony D; De Graef, Marc; Litster, Shawn; Salvador, Paul A
Abstract : Three-dimensional (3D) distributions of microstructural features in electrodes of solid oxide fuel cells (SOFCs) directly influence their electrochemical performance. Commercial grade SOFCs produced in cost-constrained environments can be expected to exhibit variations on the mesoscale (≈ hundreds of µm) of the microscale features (≈ tens of µm) that determine the local electrochemical activity. We are interested in quantitatively determining the mesoscale distributions of microscale properties in SOFC electrodes. Large volume microstructural reconstructions are required to quantify the mesoscale distributions, containing both the mean and the variance, of key microscale features that influence cell performance. In this work, we describe a serial sectioning tomography method using a Xe-plasma focused ion beam (PFIB) coupled with scanning electron microscopy (SEM) that allows for the fast reconstruction of incredibly large volumes while maintaining a resolution on the order of tens of nm, allowing for fine-scale features to be accurately quantified.